The contribution of cognitive ability and critical thinking skills on the problem solving skills of biology education profession students using case method learning - Bea Hana Siswati; Suratno Suratno (Biosfer: Jurnal Pendidikan Biologi, 2023)
Problem-solving skills have many benefits, especially for lifelong learning. Learners are equipped with these abilities to be able to survive in life and in their profession. Problem-solving skill is closely related to cognitive ability and critical thinking skill. This research aims at determining the contribution of students’ cognitive ability and critical thinking skill on their problem-solving skill. This correlational research included 127 students taking education profession courses. The collected data were analyzed using correlation regression SPSS Version 23 software. The results of the data analysis showed that students’ cognitive abilitys and critical thinking skills had a significant correlation with their problem-solving skills. The relative contribution of the cognitive ability and the critical thinking skill was 94.8%. While the effective contribution of cognitive ability and critical thinking skills toward the students’ problem-solving skills was 68.4% and 26.4% respectively. The positive correlation among these variables can be used as a basis for implementing the case method in classroom learning activities in that the implementation of the case method has positive effects on the student’s cognitive abilitys, critical thinking skills, and problem-solving skills in Biology Education students.